PRE-SERVICE TEACHERS: THE INCONSISTENCY BETWEEN THE LESSON PLANNING AND THEIR PERFORMANCE - Mahrus, Miftahul; Dewi, Ayu Ani Sartika (Universitas Muhammadiyah Metro, 2023)
Pre-service teachers must develop a good lesson plan to teach microteaching classes successfully. The lesson plan is a teaching guideline to achieve the learning objectives and successful teaching. This study focuses on the extent of the inconsistency of pre-service teachers' lesson plans and their performance and the factors that make the inconsistency. This study employed a descriptive qualitative method. The data were collected through virtual classroom observation, documentation, and interview. The participants of this study were 100 pre-service teachers. The result showed that the inconsistency of pre-service teachers' lesson plans and performance is higher than the consistency. Another result revealed that many factors make the inconsistency. The study implies that creating good lesson plans needs repeating and guidance from the experts because the product of a good lesson plan causes students' crucial learning outputs.